2017
DOI: 10.1371/journal.pone.0170335
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Heterosubtypic Immunity to Low Pathogenic Avian Influenza Viruses in Experimentally Infected Mallards

Abstract: Mallards are widely recognized as reservoirs for Influenza A viruses (IAV); however, host factors that might prompt seasonality and trends in subtype diversity of IAV such as adaptive heterosubtypic immunity (HSI) are not well understood. To investigate this, we inoculated mallards with a prevailing H3N8 low pathogenic avian influenza virus (LPAIV) subtype in waterfowl to determine if prior infection with this virus would be protective against heterosubtypic infections with the H4N6, H10N7 and H14N5 LPAIV subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
(54 reference statements)
2
13
0
Order By: Relevance
“…An important outstanding question is why so many rare genetic lineages of surface glycoproteins (H14 and divergent H4, H3, N2, and N8), and unusual subtype combinations were identified in blue-winged teals overwintering in Guatemala (23, 24) and how this diversity relates to variations over time in heterosubtypic immunity in the host population (46, 47). The sources of this diversity also remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…An important outstanding question is why so many rare genetic lineages of surface glycoproteins (H14 and divergent H4, H3, N2, and N8), and unusual subtype combinations were identified in blue-winged teals overwintering in Guatemala (23, 24) and how this diversity relates to variations over time in heterosubtypic immunity in the host population (46, 47). The sources of this diversity also remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The 50% bird infectious doses (BID 50 ) were calculated by the same method. A mock-inoculum consisting of viral transport media was used as previously described [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Effects related to homo- and heterosubtypic immunity have been reported from experimental IAV infections in mallards [ 16 20 ]. Previously, we demonstrated that cross-protective immunity between IAV subtypes results in reduced virus shedding in mallards that is positively associated with the phylogenetic relatedness of the hemagglutinin (HA) of the challenge viruses [ 21 , 22 ]. It is also possible that previous IAV infections could affect viral transmission within waterfowl populations by increasing the dose necessary to produce subsequent IAV infections.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 The mechanisms underlying these seasonal patterns are not known, but one possibility is that they are driven by the induction of humoral cross protective immunity after early infections. 5 , 6 Given the capacity for influenza viruses to spread via migratory avian hosts, as observed when H5N8 spread across North America in 2015, 7 it is important to study the mechanics underlying these seasonal dynamics. This is specifically interesting in light of cross-reactivity/cross-protection within group 1 (H1, H2, H5, H6, H8, H9, H11, H12, H13, H16, H17 and H18) and group 2 (H3, H4, H7, H10, H14 and H15) hemagglutinnin (HA) expressing viruses by stalk-reactive monoclonal antibodies isolated from humans and mice.…”
Section: Introductionmentioning
confidence: 99%